The Analysis of Protection and Fulfillment The Rights of Person with Disabilities in Gunungkidul District of Yogyakarta Province - Arni Surwanti, Ahmad Ma'aruf (Proceeding ICOMS, 2016)
The efforts to fulfill the rights of person with disabilities in various aspects like in education